2020
DOI: 10.1016/j.isci.2020.101433
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 and Small Molecule SHIP1 Allosteric Regulators Trigger Anti-inflammatory Effects through SHIP1/STAT3 Complexes

Abstract: Summary The anti-inflammatory actions of interleukin-10 (IL10) are thought to be mediated primarily by the STAT3 transcription factor, but pro-inflammatory cytokines such as interleukin-6 (IL6) also act through STAT3. We now report that IL10, but not IL6 signaling, induces formation of a complex between STAT3 and the inositol polyphosphate-5-phosphatase SHIP1 in macrophages. Both SHIP1 and STAT3 translocate to the nucleus in macrophages. Remarkably, sesquiterpenes of the Pelorol family, which we p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 63 publications
(121 reference statements)
0
36
0
Order By: Relevance
“…A similar resistance to IL-10’s anti-inflammatory action was observed in macrophages cultured in high-glucose media suggesting that hyperglycemia was responsible for the reduced anti-inflammatory function of IL-10 in T2D ( 12 ). Mechanistically, the hyporesponsiveness to IL-10 action correlated with impaired STAT3 phosphorylation under hyperglycemia and responsiveness was restored with a small molecule activator of the inositol phosphatase SHIP1 ( 12 ), highlighting the STAT3/SHIP1 axis as a potential target for restoring IL-10 action ( 4 ). Although the concept of aberrant immune cell activation in response to high glucose is well-established, recent in vitro experiments indicate that exposure to high glucose also enhances SARS-CoV-2 replication in monocytes ( 32 ).…”
Section: Il-10 Resistance As a Link Between Hyperglycemia/t2d And Sevmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar resistance to IL-10’s anti-inflammatory action was observed in macrophages cultured in high-glucose media suggesting that hyperglycemia was responsible for the reduced anti-inflammatory function of IL-10 in T2D ( 12 ). Mechanistically, the hyporesponsiveness to IL-10 action correlated with impaired STAT3 phosphorylation under hyperglycemia and responsiveness was restored with a small molecule activator of the inositol phosphatase SHIP1 ( 12 ), highlighting the STAT3/SHIP1 axis as a potential target for restoring IL-10 action ( 4 ). Although the concept of aberrant immune cell activation in response to high glucose is well-established, recent in vitro experiments indicate that exposure to high glucose also enhances SARS-CoV-2 replication in monocytes ( 32 ).…”
Section: Il-10 Resistance As a Link Between Hyperglycemia/t2d And Sevmentioning
confidence: 99%
“…If IL-10 resistance is involved in COVID-19 adverse outcomes, then recent insights into the molecular aspects of anti-inflammatory IL-10 signaling may provide clues for novel therapeutic options. Chamberlain and colleagues ( 4 ) recently reported that anti-inflammatory IL-10 signaling involves induction of a SHIP1-STAT3 complex, which translocates to the nucleus resulting in inhibition of macrophage activation and resolution of inflammatory colitis in mice. In this study, a small molecule SHIP1 agonist acted like an anti-inflammatory “IL-10 mimetic” to inhibit macrophage activation and resolve colitis in IL-10 receptor knock-out mice.…”
Section: Potential Therapeutic Avenues Targeting Il-10 Signallingmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of the closely related enzyme SHIP1 has proposed, on the basis of docking and site-directed mutagenesis, that allosteric regulators of the Pelorol family, ZPR-MN100 (formerly known as AQX-MN100) and ZPR-151, bind in the interface between the C2 and catalytic domain of SHIP1. 26 The binding site for these ligands is proposed to include a lysine residue (K681 in PDB entry 6DLG) that is approximately 23.7 Å distant from D613 coordinated by 1,2,4-dimer (6SQU) ( Figure S6 ). Thus, while the two allosteric agents ZPR-MN100 and 1,2,4-dimer occupy distinct sites, they both point to interdomain (C2-catalytic) communication as a target for therapeutic manipulation.…”
Section: Resultsmentioning
confidence: 99%
“…IL10 is a pleiotropic cytokine originally characterized as a cytokine synthesis inhibitory factor produced by murine Th2 T-cells to prevent cytokine production by murine Th1 T-cells [12], but deactivating activated macrophages is it's major in vivo function [13]. IL10 receptor (IL10R) signaling uses both the Signal Transducer and Activator of Transcription 3 (STAT3) [14][15][16] and Src Homology 2 domain-containing Inositol-5 Phosphatase 1 (SHIP1)-dependent [14,17,18] pathways to deactivate macrophages [15,[17][18][19][20]. We previously reported that SHIP1 could form a complex with STAT3 (SHIP1:STAT3) in response to IL10R signaling or through the exposure of cells to small molecules that bind to induce a conformational change in SHIP1 [14].…”
Section: Introductionmentioning
confidence: 99%